A high-strength and high-corrosion-resistant semi-solid magnesium alloy and preparation method thereof
By introducing a specific proportion of rare earth elements and metal elements into magnesium alloys and adopting advanced smelting processes and processing methods, the problems of insufficient strength and poor corrosion resistance of traditional magnesium alloys are solved, and its mechanical properties and corrosion resistance are significantly improved.
Patent Information
- Application Number
- CN202411773485.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-05
AI Technical Summary
Traditional magnesium alloys have shortcomings in strength and corrosion resistance, which limits their application under high strength requirements or harsh environmental conditions.
By introducing a specific proportion of rare earth elements Gd, Y, and metal elements Zn, Zr into the magnesium alloy, and using a smelting process that adds raw materials and SF6 and CO2 protective atmospheres in three batches under a specific volume ratio, combining semi-solid casting and rotary forging processing, the composition and microstructure of the magnesium alloy are optimized.
It significantly improves the mechanical properties and corrosion resistance of magnesium alloys, forms a denser corrosion film, effectively prevents the penetration of harmful anions, and improves the density and stability of the oxide film.
Smart Images

Figure CN119243003B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material casting, and specifically relates to a high-strength and high-corrosion-resistant semi-solid magnesium alloy and a preparation method thereof. Background Art
[0002] With the widespread application of lightweight and high-performance materials in aerospace, automotive industry, electronic equipment and other fields, magnesium alloy has attracted more and more attention because it is the lightest structural metal material (its density is only 2 / 3 of aluminum and 1 / 4 of iron).
[0003] However, although magnesium alloys have shown unparalleled advantages in lightweighting, some of their inherent performance shortcomings cannot be ignored. Traditional magnesium alloys have obvious deficiencies in strength and corrosion resistance, which to a certain extent limits their widespread application in high-strength requirements or harsh environmental conditions. In the aerospace field, aircraft need to withstand extreme flight conditions and complex climatic environments, and have extremely strict requirements on the strength, toughness and corrosion resistance of materials; in the automotive industry, with the rapid development of electric vehicles and autonomous driving technology, vehicles are increasingly in need of lightweight materials, but at the same time, these materials are also required to have good collision safety performance and corrosion resistance in long-term use.
[0004] In order to overcome these defects, it is particularly important to develop high-strength and high-corrosion-resistant magnesium alloy materials. Summary of the invention
[0005] The object of the present invention is to provide a high-strength and high-corrosion-resistant semi-solid magnesium alloy and a preparation method thereof. The high-strength and high-corrosion-resistant semi-solid magnesium alloy not only has high strength and excellent mechanical properties, but also has high corrosion resistance.
[0006] A high-strength and high-corrosion-resistant semi-solid magnesium alloy comprises, by weight percentage, 5.0% to 7.0% Gd, 2.0% to 3.0% Y, 0.5% to 1.0% Zn, 0.2% to 0.3% Zr, and the remainder is magnesium and trace amounts of inevitable impurity elements.
[0007] By introducing a specific proportion of rare earth elements Gd and Y, and metal elements Zn and Zr into magnesium alloys, the corrosion resistance of magnesium alloys can be improved while improving their mechanical properties. This may be because, on the one hand, the potential difference between the second phase Mg5 (Gd, Y) precipitated by Gd and Y and the Mg matrix is small, and the second phase is evenly distributed after semi-solid casting, forming a more uniform and weaker micro-galvanic corrosion, thereby producing a denser corrosion film, which effectively prevents the penetration of harmful anions; on the other hand, by effectively refining the grain structure, improving the mechanical properties of the material, and improving the density and stability of the oxide film, the corrosion resistance is significantly improved. The addition of Zn to magnesium alloys has a significant solid solution strengthening effect, which significantly improves the yield strength and tensile strength of the alloy. In addition, the addition of Zr to the alloy helps to optimize the microstructure, promote a more uniform grain distribution, and is beneficial to improve the mechanical properties of the alloy. Reasonable composition design and processing methods can form a good interaction between magnesium, rare earth elements, zinc and zirconium, thereby synergistically improving the mechanical properties and corrosion resistance of magnesium alloys.
[0008] The impurity elements include but are not limited to one or more of Fe, Cu, and Ni.
[0009] Preferably, the high-strength and high-corrosion-resistant semi-solid magnesium alloy has a composition, by weight percentage, of Gd: 5.97%, Y: 2.34%, Zn: 0.73%, Zr: 0.26%, and the remainder being magnesium and trace amounts of unavoidable impurity elements.
[0010] The method for preparing the high-strength and high-corrosion-resistant semi-solid magnesium alloy comprises the following steps:
[0011] S1. Weighing magnesium ingots, zinc blocks, and Mg-Gd, Mg-Y and Mg-Zr master alloys according to the weight percentages of the elements of the high-strength and high-corrosion-resistant semi-solid magnesium alloy;
[0012] S2, the raw materials are put into an induction melting furnace, and heated, stirred and kept warm under a protective atmosphere to obtain a melt;
[0013] S3, under a protective atmosphere, refining, degassing, and stirring the melt obtained in step S2, and then standing and keeping warm for 8 to 12 minutes;
[0014] S4, transferring the melt obtained in step S3 into a container, cooling it to a semi-solid zone, continuously stirring it, pouring it into a preheated mold, and air-cooling it into an ingot to obtain a magnesium alloy casting;
[0015] S5. At room temperature, the magnesium alloy casting is placed in a rotary forging die and subjected to rotary forging to obtain a semi-solid magnesium alloy with high strength and high corrosion resistance.
[0016] Preferably, the weight percentages of the metals in the Mg-Gd, Mg-Y and Mg-Zr master alloys are Mg-30Gd, Mg-30Y and Mg-30Zr respectively.
[0017] The specific operation steps of step S2 are:
[0018] A1. Put the magnesium ingot and zinc block into the induction melting furnace, heat to 715~725℃ under protective atmosphere, and keep warm for 8~12min after they are completely melted;
[0019] A2. Under protective atmosphere, add Mg-Gd and Mg-Y master alloys, and stir and keep warm for 8-12 minutes after they are completely melted into a melt; raise the temperature to 745-755°C, add Mg-Zr master alloy, and stir and keep warm for 20-30 minutes after they are completely melted into a melt.
[0020] By adding raw materials three times and controlling the temperature, the corrosion resistance and mechanical properties of magnesium alloys can be improved. This may be because the melting points of each element and the role they play in the system are different. Magnesium and zinc are the main components of magnesium alloys. Their melting temperatures are relatively low, and magnesium is highly active, so it needs to be melted in a protective atmosphere to prevent oxidation; then adding Mg-Gd and Mg-Y master alloys can not only avoid excessive local concentrations of alloying elements in the melt, thereby ensuring uniform distribution of alloying elements in the melt, but also avoid excessive volatilization and oxidation of alloying elements at high temperatures; finally, adding Mg-Zr master alloy can play a role in refining the overall grains. Adding Mg-Zr master alloy at a higher temperature can ensure that the Zr element is fully dissolved and evenly distributed in the melt. Adding alloying elements in sequence not only helps to reduce inclusions and defects in the alloy, thereby improving the density and corrosion resistance of the alloy, but also ensures uniform distribution of alloying elements in the melt, thereby improving the strength and toughness of the alloy.
[0021] Preferably, the protective atmosphere is a mixed gas of SF6 and CO2.
[0022] Preferably, the volume ratio of SF6 to CO2 is 1:(28~32).
[0023] By melting in a protective atmosphere of SF6 and CO2 at a specific volume ratio, the corrosion resistance of magnesium alloys can be improved while improving their mechanical properties. This may be because the two gases work synergistically. On the one hand, they can not only form a dense oxide film, but also cool the surface of the melt, reduce the vapor pressure of the solution, and inhibit the contact between air and the melt, thereby effectively preventing the oxidation of the magnesium alloy. On the other hand, the appropriate volume ratio of SF6 and CO2 can not only promote the grain refinement of the magnesium alloy during the melting process, reduce the defects and stress concentration points of the material, and improve its strength and toughness, but also promote the uniform distribution of alloying elements in the magnesium alloy, thereby improving its mechanical properties and corrosion resistance. Although an excessively high volume of SF6 may make the oxide film on the surface of the magnesium alloy more dense, thereby improving its corrosion resistance, it will increase environmental pollution and cost, and will also have an adverse effect on the mechanical properties of the magnesium alloy. When the volume ratio of CO2 is too high, the protective effect of the oxide film will be reduced, making the magnesium alloy more susceptible to corrosion.
[0024] Preferably, the temperature of the semi-solid zone is 590-610°C.
[0025] The selection of a semi-solid casting process at a specific temperature can improve the strength and toughness of magnesium alloys. This may be because, on the one hand, casting defects such as pores and keyholes in the alloy often become stress concentration sources, affecting the mechanical properties of the material, and in the semi-solid zone temperature described in the present invention, the mixed metal liquid of the high-strength and high-corrosion-resistant semi-solid magnesium alloy can flow in an orderly manner in the solid-liquid two-phase region, which can not only avoid the chaotic and uncontrollable macroscopic flow state of the liquid metal, thereby reducing the generation of pores, but also the volume shrinkage rate of the semi-solid metal during the solidification process is small, thereby reducing the volume of shrinkage cavities generated, and improving the strength and toughness of the magnesium alloy. On the other hand, in the semi-solid casting process, the coexistence of solid and liquid phases helps to refine the grains and improve the microstructure of the casting, thereby further improving its mechanical properties. Too low a temperature will lead to an increase in casting defects, while too high a temperature will lead to grain growth and phase change, both of which will affect its mechanical properties.
[0026] Preferably, the stirring rate of step S4 is 85-95 r / min.
[0027] Preferably, the specific conditions of the rotary forging process are: total power of 36-38 kW, rotary forging speed of 915-925 r / min, and rotary forging time of 90-120 s.
[0028] The mechanical properties of magnesium alloys can be further improved by rotary forging magnesium alloy castings and controlling the rotary forging conditions. This may be because, on the one hand, a large number of dislocations are introduced into the magnesium alloy through the rotary forging process. These dislocations will pin and entangle with each other, hindering the sliding of dislocations, thereby improving the mechanical properties of magnesium alloys. On the other hand, during the rotary forging process, the magnesium alloy castings are subjected to strong plastic deformation, which can refine the grains inside the castings, reduce the proportion of coarse grains, and promote the homogenization of the internal structure of the castings, reduce or eliminate defects (such as pores, inclusions, etc.), and further improve the overall performance of the material.
[0029] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0030] 1. The present invention provides a high-strength and high-corrosion-resistant semi-solid magnesium alloy, which can significantly improve the mechanical properties and corrosion resistance of the magnesium alloy through reasonable composition design and advanced processing methods, and provide an effective solution to the problems of insufficient strength and poor corrosion resistance encountered by traditional magnesium alloys in practical applications.
[0031] 2. The present invention can improve the corrosion resistance and mechanical properties of the magnesium alloy by introducing rare earth elements Gd and Y and metal elements Zn and Zr in specific proportions into the magnesium alloy.
[0032] 3. The present invention can improve the corrosion resistance and mechanical properties of the magnesium alloy by adding raw materials in three times and controlling the temperature.
[0033] 4. The present invention can improve the corrosion resistance and mechanical properties of the magnesium alloy by melting in a protective atmosphere of SF6 and CO2 at a specific volume ratio.
[0034] 5. The semi-solid casting process at a specific temperature selected in the present invention can improve the strength and toughness of the magnesium alloy.
[0035] 6. The present invention performs rotary forging on magnesium alloy castings and controls the rotary forging conditions, which can further improve the mechanical properties of the magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art.
[0037] Figure 1 This is a metallographic diagram of the high-strength and high-corrosion-resistant semi-solid magnesium alloy described in Example 1 of the present invention.
[0038] Figure 2 This is the corrosion morphology of the high-strength and high-corrosion-resistant semi-solid magnesium alloy described in Example 1 of the present invention after being immersed in 3.5wt% NaCl for 7 days.
[0039] Figure 3 This is the surface 3D corrosion morphology of the high-strength and high-corrosion-resistant semi-solid magnesium alloy described in Example 1 of the present invention after being immersed in 3.5wt% NaCl for 7 days.
[0040] Figure 4 This is an EIS impedance curve diagram of the high-strength and high-corrosion-resistant semi-solid magnesium alloy described in Example 1 of the present invention and Comparative Example 1 after being immersed in 3.5wt% NaCl for 7 days. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] The present embodiment provides a high-strength and high-corrosion-resistant semi-solid magnesium alloy, wherein the high-strength and high-corrosion-resistant semi-solid magnesium alloy has a composition, by weight percentage, of Gd: 5.97%, Y: 2.34%, Zn: 0.73%, Zr: 0.26%, and the remainder is magnesium and trace amounts of unavoidable impurity elements.
[0044] The method for preparing the high-strength and high-corrosion-resistant semi-solid magnesium alloy comprises the following steps:
[0045] S1. Weighing magnesium ingots, zinc blocks, and Mg-30Gd, Mg-30Y and Mg-30Zr master alloys according to the weight percentages of the elements of the high-strength and high-corrosion-resistant semi-solid magnesium alloy;
[0046] S2, the raw materials are put into an induction melting furnace, and heated, stirred and kept warm under a protective atmosphere to obtain a melt;
[0047] S3, under a protective atmosphere, refining, degassing, and stirring the melt obtained in step S2, and then standing and keeping warm for 10 minutes;
[0048] S4, transferring the melt obtained in step S3 into a container, cooling it to a semi-solid zone, continuously stirring it, pouring it into a preheated mold, and air-cooling it into an ingot to obtain a magnesium alloy casting;
[0049] S5. At room temperature, the magnesium alloy casting is placed in a rotary forging die and subjected to rotary forging to obtain a semi-solid magnesium alloy with high strength and high corrosion resistance.
[0050] The specific operation steps of step S2 are:
[0051] A1. Put the magnesium ingot and zinc block into the induction melting furnace, heat to 720℃ under protective atmosphere, and keep warm for 10 minutes after they are completely melted;
[0052] A2. Under a protective atmosphere, add Mg-Gd and Mg-Y master alloys, and stir and keep them warm for 10 minutes after they are completely melted into a melt; raise the temperature to 750°C, add Mg-Zr master alloy, and stir and keep them warm for 20 minutes after they are completely melted into a melt.
[0053] The protective atmosphere is a mixed gas of SF6 and CO2 with a volume ratio of 1:30.
[0054] The temperature of the semi-solid zone is 600°C.
[0055] The stirring rate of step S4 is 90 r / min.
[0056] The specific conditions of the rotary forging process are: total power of 37 kW, rotary forging speed of 920 r / min, and rotary forging time of 100 s.
[0057] Example 2
[0058] The difference between this embodiment and embodiment 1 is that the high-strength and high-corrosion-resistant semi-solid magnesium alloy has the following components, by weight percentage: Gd: 5.26%, Y: 2.24%, Zn: 0.55%, Zr: 0.23%, and the remainder is magnesium and trace amounts of unavoidable impurity elements.
[0059] The temperature of the semi-solid zone was 590°C.
[0060] The specific conditions of the rotary forging process are: total power of 37 kW, rotary forging speed of 920 r / min, and rotary forging time of 90 s.
[0061] Example 3
[0062] The difference between this embodiment and embodiment 1 is that the high-strength and high-corrosion-resistant semi-solid magnesium alloy has the following components, by weight percentage: Gd: 6.86%, Y: 2.93%, Zn: 0.85%, Zr: 0.28%, and the remainder is magnesium and trace amounts of unavoidable impurity elements.
[0063] The temperature of the semi-solid zone was 610°C.
[0064] The specific conditions of the rotary forging process are: total power of 37 kW, rotary forging speed of 920 r / min, and rotary forging time of 120 s.
[0065] Example 4
[0066] The difference between this embodiment and embodiment 1 is that the high-strength and high-corrosion-resistant semi-solid magnesium alloy has the following components, by weight percentage: Gd: 5.86%, Y: 2.74%, Zn: 0.95%, Zr: 0.21%, and the remainder is magnesium and trace amounts of unavoidable impurity elements.
[0067] The temperature of the semi-solid zone was 605°C.
[0068] The specific conditions of the rotary forging process are: total power of 37 kW, rotary forging speed of 920 r / min, and rotary forging time of 120 s.
[0069] Example 5
[0070] The difference between this embodiment and embodiment 1 is that the high-strength and high-corrosion-resistant semi-solid magnesium alloy has the following components, by weight percentage: Gd: 6.33%, Y: 2.01%, Zn: 0.98%, Zr: 0.29%, and the remainder is magnesium and trace amounts of unavoidable impurity elements.
[0071] The temperature of the semi-solid zone was 610°C.
[0072] The specific conditions of the rotary forging process are: total power of 37 kW, rotary forging speed of 920 r / min, and rotary forging time of 90 s.
[0073] Comparative Example 1
[0074] The difference between this comparative example and Example 1 is that the high-strength and high-corrosion-resistant semi-solid magnesium alloy has the following components, by weight percentage: Gd: 6.01%, Y: 2.31%, Zn: 0.78%, Zr: 0.23%, and the remainder is magnesium and trace amounts of unavoidable impurity elements.
[0075] The temperature of the semi-solid zone is 550°C.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 1 is that the specific conditions of the rotary forging process are: the total power is 37 kW, the rotary forging speed is 920 r / min, and the rotary forging time is 60 s.
[0078] Comparative Example 3
[0079] The difference between this comparative example and Example 1 is that the high-strength and high-corrosion-resistant semi-solid magnesium alloy has the following components, by weight percentage: Gd: 7.42%, Y: 2.54%, Zn: 0.67%, Zr: 0.25%, and the remainder is magnesium and trace amounts of unavoidable impurity elements.
[0080] Comparative Example 4
[0081] The difference between this comparative example and Example 1 is that the high-strength and high-corrosion-resistant semi-solid magnesium alloy has the following components, by weight percentage: Gd: 5.78%, Y: 4.01%, Zn: 0.65%, Zr: 0.23%, and the remainder is magnesium and trace amounts of unavoidable impurity elements.
[0082] Comparative Example 5
[0083] The difference between this comparative example and Example 1 is that the specific operation steps of step S2 are:
[0084] Put magnesium ingot, zinc block, Mg-Gd, Mg-Y master alloy and Mg-Zr master alloy into an induction melting furnace, heat to 720°C under a protective atmosphere, keep warm for 20 minutes after complete melting; heat to 750°C, stir and keep warm for 20 minutes.
[0085] Comparative Example 6
[0086] The difference between this comparative example and Example 1 is that the protective atmosphere is SF6.
[0087] Performance Testing
[0088] The high strength and high corrosion resistance semi-solid magnesium alloy obtained in Example 1 was subjected to metallographic microscopic analysis. Figure 1 The obtained high-strength and high-corrosion-resistant semi-solid magnesium alloy was immersed in a 3.5% NaCl aqueous solution for seven days to test the corrosion rate. The morphology of the sample of Example 1 after seven days of corrosion was analyzed. See the photo. Figure 2 and Figure 3 The mechanical properties of the prepared high-strength and high-corrosion-resistant semi-solid magnesium alloy were tested. The results are shown in Table 1. The EIS impedance curves of the samples of Example 1 and Comparative Example 1 after immersion in 3.5% NaCl aqueous solution for 7 days are shown in Table 1. Figure 4 .
[0089] Table 1 Measurement results
[0090]
[0091] According to statistics, the high-strength and high-corrosion-resistant semi-solid magnesium alloy prepared in Examples 1 to 5 of the present invention has a weight loss corrosion rate of 0.45 to 0.60 mm / y in a 3.5wt% NaCl immersion test. The semi-solid magnesium alloy prepared by optimizing the formula and process shows excellent corrosion resistance. The alloy forms a dense corrosion film during the immersion test, effectively blocking the penetration of chloride ions, thereby significantly reducing the corrosion rate of the matrix. The yield strength of the high-strength and high-corrosion-resistant semi-solid magnesium alloy is 240 to 250 MPa, and the ultimate tensile strength is 320 to 350 MPa. After reasonable element ratios and process preparation parameters, the microstructure, stress state and phase change control of the magnesium alloy are significantly optimized, thereby significantly improving its mechanical properties. The low molding temperature in Comparative Example 1 not only leads to uneven phase distribution during the phase change process, thereby accelerating the local micro-galvanic corrosion of the magnesium alloy, thereby accelerating the overall corrosion rate of the magnesium alloy, but also leads to a decrease in the fluidity of the alloy, thereby causing the casting to form cavities, inclusions or defects, reducing the overall strength of the magnesium alloy. In comparative example 2, the rotary forging time is too short, which not only fails to fully refine the grains, but also leads to larger grains, so that larger grains form stress concentration points during the corrosion process, thereby accelerating local corrosion, affecting the overall corrosion resistance of the alloy, but also causes uneven deformation of the magnesium alloy, forming local stress concentration, more prone to cracks or fractures, and reducing its overall mechanical properties. In comparative examples 3-4, the rare earth Gd and Y element contents are too high, respectively, which not only makes the second phase precipitated excessive, but also produces more electrochemical corrosion to the surrounding matrix in a corrosive environment, accelerates local corrosion, thereby greatly reducing the overall corrosion resistance of the magnesium alloy, and also makes the processing performance of the magnesium alloy worse, thereby reducing the yield strength and ultimate tensile strength of the magnesium alloy. In comparative example 5, the raw materials are not added for smelting three times, which not only increases the inclusion and defect content in the alloy, affects the density and corrosion resistance of the alloy, but also makes the distribution of alloy elements in the melt uneven, affecting the strength of the alloy. In Comparative Example 6, CO2 was not added as a protective atmosphere. Although it had little effect on the corrosion resistance of the alloy, it affected the grain refinement of the magnesium alloy during the smelting process, resulting in the inability to reduce material defects and stress concentration points, which in turn affected the mechanical properties of the magnesium alloy.
[0092] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength and high-corrosion-resistant semi-solid magnesium alloy, characterized in that: In terms of weight percentage, its composition is Gd: 5.97%, Y: 2.34%, Zn: 0.73%, Zr: 0.26%, the balance is magnesium and trace amounts of unavoidable impurity elements; the preparation method of the high-strength and high-corrosion-resistant semi-solid magnesium alloy comprises the following steps: S1. Weighing magnesium ingots, zinc blocks, and Mg-Gd, Mg-Y and Mg-Zr master alloys according to the weight percentages of the elements of the high-strength and high-corrosion-resistant semi-solid magnesium alloy; S2, the raw materials are put into an induction melting furnace, and heated, stirred and kept warm under a protective atmosphere to obtain a melt; S3, under a protective atmosphere, refining, degassing, and stirring the melt obtained in step S2, and then standing and keeping warm for 8 to 12 minutes; S4, transferring the melt obtained in step S3 into a container, cooling it to a semi-solid zone, continuously stirring it, pouring it into a preheated mold, and air-cooling it into an ingot to obtain a magnesium alloy casting; The temperature of the semi-solid zone is 590-610°C; S5. At room temperature, the magnesium alloy casting is placed in a rotary forging die and subjected to rotary forging to obtain a semi-solid magnesium alloy having high strength and high corrosion resistance; The specific operation steps of step S2 are: A1. Put the magnesium ingot and zinc block into the induction melting furnace, heat to 715~725℃ under protective atmosphere, and keep warm for 8~12min after they are completely melted; A2. Under protective atmosphere, add Mg-Gd and Mg-Y master alloys, completely melt them into a melt, stir and keep warm for 8-12 minutes; heat to 745-755℃, add Mg-Zr master alloy, completely melt them into a melt, stir and keep warm for 20-30 minutes; The protective atmosphere is a mixed gas of SF6 and CO2.
2. The high-strength and high-corrosion-resistant semi-solid magnesium alloy according to claim 1, characterized in that: The impurity elements include one or more of Fe, Cu, and Ni.
3. The high-strength and high-corrosion-resistant semi-solid magnesium alloy according to claim 1, characterized in that: The weight percentages of the metals in the Mg-Gd, Mg-Y and Mg-Zr master alloys are Mg-30Gd, Mg-30Y and Mg-30Zr respectively.
4. The high-strength and high-corrosion-resistant semi-solid magnesium alloy according to claim 1, characterized in that: The volume ratio of SF6 and CO2 is 1:(28~32).
5. The high-strength and high-corrosion-resistant semi-solid magnesium alloy according to claim 1, characterized in that: The specific conditions of the rotary forging process are: total power of 36-38 kW, rotary forging speed of 915-925 r / min, and rotary forging time of 90-120 s.
Citation Information
Patent Citations
Magnesium alloy and preparation method and application thereof
CN104651694A
High-strength rare earth magnesium alloy capable of preparing large-size ingot and method
CN105349863A